2022
DOI: 10.1140/epjc/s10052-022-10480-0
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic flow correlations in Au+Au reactions at 1.23 AGeV: a new testing ground for the equation-of-state and expansion geometry

Abstract: Correlations between the harmonic flow coefficients $$v_1$$ v 1 , $$v_2$$ v 2 , $$v_3$$ v 3 and $$v_4$$ v 4 of nucleons in semi-periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Here, Fig. 1 shows the first four symmetric flow coefficients v sym has a positive correlation with the longitudinal momentum and reflects the strength of the bounce off of the two incoming nuclei as was discussed in detail in [23] and we observe as expected that with a stiffer equation of state the bounce off becomes more pronounced due to larger pressure (density) gradients. The elliptic flow v sym 2 is negative around zero longitudinal momenta and exhibits a convex shape.…”
Section: Results: Momentum Dependence Of the Novel Flow Coefficientssupporting
confidence: 71%
See 1 more Smart Citation
“…Here, Fig. 1 shows the first four symmetric flow coefficients v sym has a positive correlation with the longitudinal momentum and reflects the strength of the bounce off of the two incoming nuclei as was discussed in detail in [23] and we observe as expected that with a stiffer equation of state the bounce off becomes more pronounced due to larger pressure (density) gradients. The elliptic flow v sym 2 is negative around zero longitudinal momenta and exhibits a convex shape.…”
Section: Results: Momentum Dependence Of the Novel Flow Coefficientssupporting
confidence: 71%
“…[22]. UrQMD has been further highly successful in describing and predicting directed, elliptic, triangular as well as quadrangular flow of nucleons and light clusters [13,14] and their correlations [23].…”
Section: Model Setup and Flow Extractionmentioning
confidence: 99%
“…A recent study has shown that this approach is consistent with MST calculations for cluster production [13]. UrQMD has already been successfully applied to calculate direct and elliptic flow and higher-order flow components [5,6,14] of nucleons and light clusters in the investigated energy regime and has recently demonstrated its abilities to further describe larger clusters (t, 3 He) [15].…”
Section: Simulation Set-upmentioning
confidence: 69%
“…After the compilation of this comparison, several updates of the transport codes used here were published or are in progress: UrQMD version 3.5 [404][405][406] was released, JAM, previously written in Fortran, was rewritten in C++ introducing several updates to the mean-field potentials in version 2.1 [407,408] and the GiBUU code in its recent version of 2021 was released. Since the models used here do not apply dedicated mechanisms for producing light clusters, we restrict the comparison to protons only.…”
Section: Transport Model Simulationsmentioning
confidence: 99%